Pengembangan Model Aplikasi Administrasi Pelayanan Kesehatan di Puskemas dengan Cloud Computing Berbasiskan Open Source - Honni, Honni (Bina Nusantara University, 2013)
Puskemas as community health centers becomes one of the main focuses of development on the agenda of the Government of Indonesia beside education. Therefore, we purpose to develop an affordable online system of health care administration based on open source using cloud computing approach. It can be used for collecting data of patients, diseases, and treatment of patients at Puskesmas. The methods used are literature study related to cloud computing, survey design and data collection infrastructure of information technology thatcan be applied to online health services, analysis of survey data on actual conditions in some centers and other health care centers in Jakarta, then making model of online health services such as physician consulting, prescribing and disease diagnosis. The result is a web-based application system of health care administration of Puskesmas, which utilizes cloud computing technology and development architectures that are both modular and dynamic. The application model combines the benefits of open-source applications with a flexible design system. It also supports mobile devices to improve the quality of patient care. Web-based network structure allows both online and inter-section between institutions which can be accessed anytime, anywhere, through mobile devices.Development application model is also adapted to the function of the business processes and administrative processes that exist in Puskesmas throughout Indonesia. Each model is also expected to be integrated to optimize efficiency and has been adapted to the service system of Dinas Kesehatan and Health Ministery.